Targeted repair of heart injury by stem cells fused with platelet nanovesicles. (January 2018) - Tang, Junnan; Su, Teng; Huang, Ke; Dinh, Phuong-Uyen; Wang, Zegen; Vandergriff, Adam; Hensley, Michael; Cores, Jhon; Allen, Tyler; Li, Taosheng; Sproul, Erin; Mihalko, Emily; et al.
Abstract Stem cell transplantation, as used clinically, suffers from low retention and engraftment of the transplanted cells. Inspired by the ability of platelets to recruit stem cells to sites of injury on blood vessels, we hypothesized that platelets might enhance the vascular delivery of cardiac stem cells (CSCs) to sites of myocardial infarction injury. Here, we show that CSCs with platelet nanovesicles fused onto their surface membranes express platelet surface markers that are associated with platelet adhesion to injury sites. We also find that the modified CSCs selectively bind collagen-coated surfaces and endothelium-denuded rat aortas, and that in rat and porcine models of acute myocardial infarction the modified CSCs increase retention in the heart and reduce infarct size. Platelet-nanovesicle-fused CSCs thus possess the natural targeting and repairing ability of their parental cell types. This stem cell manipulation approach is fast, straightforward and safe, does not require genetic alteration of the cells, and should be generalizable to multiple cell types. The attachment of platelet nanovesicles to the surface of cardiac stem cells increases the retention of the cells delivered to the heart and reduces infarct size in rat and pig models of acute myocardial infarction.